The Influence of Personal Communication by Room Attendants on Guest Satisfaction at Manhattan Hotel - Suesilowati, Suesilowati; Rusli, Ahmad; Frisiska, Frisiska (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the influence of educational level, gender, and personal communication skills of room attendants on guest satisfaction at Hotel Manhattan Jakarta. A quantitative explanatory approach was employed, with purposive sampling used to select guests who met specific criteria, including a minimum one-night stay and prior interaction with a room attendant. Data were collected through a structured Likert-scale questionnaire and tested for validity and reliability using Pearson’s Product Moment correlation and Cronbach’s Alpha. The results of the study indicate that all questionnaire items are valid and reliable, with Cronbach’s Alpha values exceeding 0.86 for both personal communication and guest satisfaction variables. Linear regression analysis shows that personal communication has a significant positive effect on guest satisfaction, as evidenced by a t-value of 13.078 and a significance level of 0.000. The regression model Y=15.452+0.910XY = 15.452 + 0.910X suggests that each one-unit improvement in personal communication score increases guest satisfaction by 0.910 units. The coefficient of determination (R²) of 0.673 indicates that 67.3% of the variation in guest satisfaction is explained by personal communication, while the remaining 32.7% is influenced by other factors not covered in this study. These findings highlight the crucial role of personal communication in service delivery. For practical implications, hotel management should prioritize continuous training programs aimed at enhancing room attendants’ interpersonal skills, empathy, and responsiveness, as these factors directly contribute to guest satisfaction, positive word-of-mouth, and long-term brand reputation